The Effect of Systematic Risk and Sustainability Report Disclosure on Company Value - Lazuardy, Alvin; Fidiana, Fidiana; Fadjrih Asyik, Nur (Jurnal Manajemen Bisnis, 2024)
Company value is very important in an effort to gain attention from every investor. So in increasing this value, companies need to pay attention to the influence of systematic risk and Sustainability Report Disclosure on company value. The purpose of this study is to determine the effect of systematic risk and sustainability report disclosure on company value. The type of research used in this study is quantitative research. The sample in this study was companies listed on the Sri-Kehati Index for the 2020-2022 period, totaling 25 companies. The data analysis technique used multiple linear regression analysis and hypothesis testing. The results of this study indicate that Systematic Risk has a positive but insignificant effect on the value of listed companies. The economic dimension of Sustainability Report Disclosure has a significant positive effect on company value. The social dimension of Sustainability Report Disclosure has a significant positive effect on the value of listed companies. The environmental dimension of Sustainability Report Disclosure has a significant positive effect on the value of companies listed on the Sri-Kehati Index for the 2020-2022 period. Companies should maintain and pay attention to company value. Namely by paying attention to the market price per share and the book value per share. Because the higher the value of the company, the greater the level of prosperity that will be received by shareholders.